Population dynamics of Pseudomonas savastanoi pv. phaseolicola in bean, throughout the epiphytic and pathogenic phases - Marques, Abi Soares dos Anjos; Samson, Régine (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to monitor traits of the life cycle of Pseudomonas savastanoi pv. phaseolicola, in order to better understand the outbreak of bean halo blight, originating from a bacterial population in asymptomatic plants. Five experiments were conducted in the field, in greenhouses, and in humidity chambers. Changes in population size were evaluated in three field plantings, by introducing the bacteria in contamination focal points and observing the weather conditions favoring an outbreak. The dispersion of the bacteria in the field was followed by isolation and Bio‑PCR analysis. Two assays were conducted in greenhouses and humidity chambers to evaluate the effect of leaf age on disease expression and the relationship between population level and number of leaf spots. The bacteria multiply intensively when in contact with a compatible host and reach high population sizes, with or without symptoms. The most favorable factor for bacterial multiplication and symptom triggering was water, and its role in the changeover from the epiphytic to the pathogenic phase might be linked to rainfall volume and intensity. Bacterial asymptomatic dispersion in the field is greater than disease emergence. In Brazil, the bacteria should be categorized as a present quarantine pest.